Farmers' Mental Health and the Need for Agro-Nursing-Based Nursing Interventions in the Agricultural Area of Jember District - Erti Ikhtiarini Dewi; Enggal Hadi Kurniyawan; Fitrio Deviantony; Yeni Fitria (GLOBAL HEALTH SCIENCE GROUP, 2025)
The agricultural sector faces with various challenges that can affect the psychological condition of farmers. These challenges include crop yield uncertainty, extreme weather, market price fluctuations, debt, and high workloads. This pressure can cause stress, anxiety, and even depression among farmers, who often receive little attention from the health system, including nursing. Objective: This research aims to identify farmers' mental health and the need for agro-nursing-based nursing interventions. Method: This research is descriptive research with a survey method. Respondents were determined using cluster random sampling, and a sample of 227 respondents was obtained. The research instrument to measure farmers' mental health uses the SRQ-20 and the need for nursing intervention uses an instrument prepared by researchers based on the Indonesian Nursing Intervention Standard (SIKI) guidelines. Results: The research results showed that 30.5% of farmers were at risk of mental health problems (SRQ score >=6). The most common symptom of anxiety experienced was not sleeping soundly (45.9%). The most common cognitive symptom experienced was difficulty making decisions (35.1%). The most common somatic symptom experienced was headache (40.5%). The most common symptom of depression experienced was loss of interest in various things (43.3%). Nursing interventions required by farmers include the need for psychological education (72%), therapeutic support (81%), and advanced therapy (43%). Conclusions: Farmers often face social and economic challenges, including income uncertainty, social isolation in rural areas, and limited access to mental health services. Farmers usually work in remote areas, making it difficult for them to accessexisting mental health facilities. Agro-nursing-based nursing can develop intervention programs in local communities, helping farmers and their families easily access mental health support. Farmers are one of the professions that are at risk of experiencing mental health problems due to the demands of their work, so they require mental nursing intervention.